Medicinal plants used by traditional healers in Pagadian City, Zamboanga del Sur, Philippines [Research note] - Fabie-Agapin, Julienne Stephanie (2020)
The documentation of plants used as medicine is an important baseline for possible extraction, isolation, characterization, and chemical modification of important chemical compounds. This study aims to determine the plants used as medicine by traditional healers in Pagadian City, Zamboanga del Sur, Philippines. A total of 80 plants were mentioned by 11 traditional healers, who willingly shared their knowledge on medicinal plants. These plants were all recorded but only 71 plants belonging to 40 families were collected and identified. The remaining nine were only mentioned but no actual photos were taken and collected because these plants were inaccessible during the collection period and/or may have withered already. The botanical families with the highest number of species were represented by the families Lamiaceae and Moraceae (6), followed by Euphorbiaceae and Fabaceae (5). The most commonly used plant parts for herbal medicines are the leaves, and the most employed method of preparation is decoction. Among the illnesses mentioned for herbal medication were cancer (as the most cited), followed by kidney problems. This study also documented plants that are prepared in mixtures to treat illnesses like severe cough, severe diarrhea, and varicose veins. The information recorded and presented in this study may be useful for future phytochemical and pharmacological studies. (Author's abstract)